The incomparable God readings in biblical theology - Strawn, Brent A. 1970-; Cornell, Collin 1988-; Walker, Justin 1987- (Chicago Wm. B. Eerdmans Publishing Co., 2023)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Author's Preface -- Introduction -- List of Abbreviations -- Part 1: Readings -- 1. From Imago to Imagines: The Image(s) of God in Genesis -- 2. Yhwh's Poesie: The Gnadenformel, the Book of Exodus, and Beyond -- 3. Keep/Observe/Do-Carefully-Today! The Rhetoric of Repetition in Deuteronomy -- 4. Slaves and Rebels: Inscription, Identity, and Time in the Rhetoric of Deuteronomy -- 5. The Art of Poetry in Psalm 137: Movement, Reticence, Cursing -- 6. Revisiting Elisha and the Bears: Can Modern Christians Read- That Is, Pray-the "Worst Texts" of the Old Testament? -- Part 2: Biblical Theology -- 7. And These Three Are One: A Trinitarian Critique of Christological Approaches to the Old Testament -- 8. "Israel, My Child": The Ethics of a Biblical Metaphor -- 9. What Would (or Should) Old Testament Theology Look Like If Recent Reconstructions of Israelite Religion Were True? -- 10. The Old Testament and Participation with God (and/in Christ?): (Re)reading the Life of Moses with Some Help from Gregory of Nyssa -- 11. Tolkien's Orcs Meet the Bible's Canaanites: The Dynamics of Reading Well … or Not (Or, How to Critique Scripture and Still Call It Scripture) -- 12. Docetism, Käsemann, and Christology: Can Historical Criticism Help Christological Orthodoxy (and Other Theology) After All? -- Part 3: Practice -- 13. Is God Always Anything? -- 14. On Pharaohs: Egyptian and Otherwise -- 15. Designated Readers: Deuteronomy's Portrait of the Ideal King- or Is It Preacher? -- 16. On Priesting -- 17. Four Thoughts on Preaching and Teaching the Bible- Mostly the Old Testament -- 18. On Not Bifurcating: Faith and Scholarship in the Life of a Bible Professor -- Acknowledgments -- Bibliography.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books